Sleep Quality and Skin Type as Factors Associated with the Incidence of Acne Vulgaris - Lessya Jhonvini; Lonah; Meiliyana Wijaya; Robi Irawan; Mariani Santosa (Jurnal Kesehatan Masyarakat, 2025)
Acne vulgaris is a skin disease caused by chronic inflammation in the pilosebaceous unit, which produces sebum. The factors causing acne vulgaris are multifactorial and interact with each other. Medical students are a subgroup of society who are vulnerable to experiencing sleep disorders. Therefore, this study aims to explore the relationship between acne and sex, sleep quality, and skin type, especially in medical students. This research uses survey methods and analytical observation with a cross-sectional approach. The sampling technique is stratified random sampling. Validated questionnaires were used to assess sleep quality and skin type. Univariate analysis showed that of the 85 participants, the majority were female and aged 20 years. The prevalence of acne in this study was 52.9%. Most respondents had poor sleep quality (63.5%) and oily skin (69.4%). Based on bivariate analysis, acne vulgaris was significantly related to sleep quality (p=0.046) and skin type (p=0.025). Multivariate analysis showed that skin type had the most robust relationship with acne vulgaris (OR = 2.876; 95% CI = 1.077-7.685).